Pengaruh Program Kerja dan Evaluasi Terhadap Kinerja Pegawai Dinas Kearsipan dan Perpustakaan Kabupaten Ogan Komering Ulu - Mahrudin Saputra; Fifian Permata Sari; Rini Efrianti (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of work programs and evaluations on the performance of employees at the Archives and Library Service of OKU Regency. The study population consisted of 37 respondents. Quantitative methods were used, using multiple linear regression analysis. The analysis results showed that the t-value for each variable, Work Program (X1), was 9.081 and Evaluation (X2), was 3.391. These values ​​were greater than the critical t-value of 2.032, indicating that all variables significantly influence the performance of employees at the Archives and Library Service of OKU Regency. The calculated F-value of 245.883 was greater than the critical F-value of 3.28, indicating that the Work Program and Evaluation together significantly influence the performance of employees at the Archives and Library Service of OKU Regency. The coefficient of determination (R-squared) is 0.935, indicating that 93.5% of employee performance (Y) can be explained by the Work Program (X1) and Evaluation (X2) variables, while the remaining 6.5% is influenced by other variables not examined in this study.